Analisis Sintaktik Frasa dalam Komentar Pembaca Manga Boruto: Naruto Next Generation Chapter 001 - Imaniah , Annisa (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The purposes of this study are to found and to analyse some phrases and sentence patterns that are used in the reader's comments of Manga Boruto: Naruto Next Generation Chapter 001using tree diagram theory. In this case, the aims of this study are: (1) To find out the phrases used in the reader's comments of Manga Boruto: Naruto Next Generation Chapter 001.(2)To find out the sentence patterns found in the reader's comments of Manga Boruto: naruto next generation chapter 001. The object of this study was reader’s comments of Manga Boruto: Naruto Next Generation Chapter 001. The method of this study is using qualitative analysis. To get the data, the writer uses three steps in analysing data by Creswell. There are: preparing and organizing, coding, and representing the data. The finding of this study as follows: (1) There were 5 types of phrases, there are: Noun Phrase (NP), Verb Phrase (VP), Adjective Phrase (Adj P), Adverb Phrase (Adv P), and Prepositional Phrase (PP). (2) There were 5 sentence patterns in Westlife’s song lyrics, there are: Pattern1: S ? NP + VP, Pattern2: NP ? Det + N, NP ? Pronoun or Noun, NP ? NP + S, Pattern3: VP ? V + NP, VP ? V + Adv P, VP ? V + Adj.P, VP ? M + V + NP, Pattern4: Compound ? S1 + Conj + S2, Pattern5: Complex ? Clause1 + Clause2, Pattern6: PP ? Prep + N.